If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + 8) + 4 = 8(t + 2) * 3 Reorder the terms: 3(8 + t) + 4 = 8(t + 2) * 3 (8 * 3 + t * 3) + 4 = 8(t + 2) * 3 (24 + 3t) + 4 = 8(t + 2) * 3 Reorder the terms: 24 + 4 + 3t = 8(t + 2) * 3 Combine like terms: 24 + 4 = 28 28 + 3t = 8(t + 2) * 3 Reorder the terms: 28 + 3t = 8(2 + t) * 3 Reorder the terms for easier multiplication: 28 + 3t = 8 * 3(2 + t) Multiply 8 * 3 28 + 3t = 24(2 + t) 28 + 3t = (2 * 24 + t * 24) 28 + 3t = (48 + 24t) Solving 28 + 3t = 48 + 24t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-24t' to each side of the equation. 28 + 3t + -24t = 48 + 24t + -24t Combine like terms: 3t + -24t = -21t 28 + -21t = 48 + 24t + -24t Combine like terms: 24t + -24t = 0 28 + -21t = 48 + 0 28 + -21t = 48 Add '-28' to each side of the equation. 28 + -28 + -21t = 48 + -28 Combine like terms: 28 + -28 = 0 0 + -21t = 48 + -28 -21t = 48 + -28 Combine like terms: 48 + -28 = 20 -21t = 20 Divide each side by '-21'. t = -0.9523809524 Simplifying t = -0.9523809524
| 14-x=-38 | | 46.50-15=5.25 | | 13x-4=-43 | | -4(-4+x)=54 | | 3-7(2-x)=5k+2(-2-4x) | | 35+2x=58 | | 8x-8=6x+28 | | 8a+3-5a-2a= | | (X-1)+5+x=12 | | 2g+4=24 | | 5.7+6.6= | | (7x+15)=(10-9) | | 36x=8-14p | | 3=17-7n | | 14=4(7-8p)-6(4p-7) | | 250+14(h)=22(h) | | -y+3-3=-6 | | 5(2x-3)=7x+15 | | 11x-15=40 | | 3f-12=3(f+12) | | 5.25+15=46.50 | | 8x-3=3x-7 | | -4r+4r=8-4r+3r | | 130+40c=270 | | 4b-11=5 | | 15x-54=66 | | 3t^2-14t-22=0 | | (4x-1)(2x^2+3)= | | 64x^2-644x+1552=0 | | -6x+3=-39 | | .3x+5=6 | | k+9=6(k-1) |